Scripture, Piety and the Practice of Peace in Nineteenth-Century New Zealand Missions. (August 2019) - Troughton, Geoffrey
Abstract : Nineteenth-century missionary activity is more commonly associated in historiography with the violence of colonisation and imperialism than with peace. Nevertheless, in some places, rhetoric proclaiming Christianity as a peace-bringer became tied more decisively with the preaching of peace as an ethical imperative. This article explores the emergence and cultivation of a peace gospel in the mission to Māori in nineteenth-century New Zealand. It argues that formations of piety, especially bible reading, were central to the inculcation of an influential peace ethic.